Myopia in school children from high mountain region of Nepal - Adhikari, Sirjana (Nepalese Journal of Ophthalmology, 2013)
Objective: Myopia is emerging as a public health problem in school going children. Prevalence of myopia differs in different geographical areas, race, ethnic groups and socioeconomic background. Purpose of this study was to find out myopia prevalence in schoolchildren from very high mountain region of Nepal. Materials and methods: It was a cross sectional descriptive study. Vision screening was conducted in Snowland School among the children who come from high mountain region. Vision screening was done by volunteers using standard Snellen’s chart. Those who failed screening test underwent a detailed ophthalmological examination by a pediatric ophthalmologist. Results: A total of 140 children had their vision assessed. Mean age was 13.9yrs (±2.8yrs SD). On screening, 28.5% children (n=40) had vision less than 6/9 in at least one eye. Seven children were already wearing myopic glasses, among which only 2 had vision 6/9 or better. Out of 40 children, 10% (n=4) had vision 6/9 or better and 90% (n=36) had refractive error. Out of these 36 children, myopia was present in all (100%).Hence prevalence of Myopia in total school population was 27% (n=38).All the children had simple Myopia from 0.5D-3.5D. After refractive correction, all the children had best corrected visual acuity of 6/9 or better. 86 % (n=120) children never had their eyes checked before. Conclusion The study showed high prevalence of myopia and was only ocular morbidity present in children. The result of this study can be a baseline in conducting large population based study in children from high mountains of Nepal. Nepal J Ophthalmol 2013; 5(10): 246-249 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8737